A systematic review and meta-analysis on the association between androgenic alopecia and the risk of metabolic syndrome - Afsaneh Sadeghzadeh-Bazargan; Masoumeh Roohaninasab; Farnoosh Seirafianpour; Mahsa Shemshadi; Arezoo Mohammadi; Samaneh Mozafarpoor; Azadeh Goodarzi (Sociedade Brasileira de Dermatologia (SBD), 2022)
This study conducted a systematic review of studies on the relationship between androgenic alopecia and metabolic syndrome. We performed a comprehensive review of databases including PubMed, Web of Knowledge, Google Scholar, Scopus, and Embase, and extracted relevant articles published from 2010 to 2018. The case reports, review articles, or studies lacking full-text articles were excluded. We examined nine studies for the meta-analysis step. The results showed a significant relationship between alopecia and metabolic syndrome (OR = 2.81; CI 95% = 2.16-3.66; I2 = 73%; P = 0.0003). There is a significant correlation between androgenic alopecia and metabolic syndrome.